Cardiovascular events among recipients of hematopoietic stem cell transplantation. (14th October 2021) - Aghel, N; Lui, M; Mian, H; Khalaf, D; Hillis, C; Petropoulos, J; Wang, V; Leber, B; Lipton, J; Walker, I; Leong, D
Abstract: Background: Allogeneic and autologous hematopoietic stem cell transplantation (HSCT) are potential curative treatments for several hematological malignancies (1). Survival after HSCT has improved over the last decade, but survivors remain at risk for health issues after transplantation. Cardiovascular complications after HSCT are increasingly recognized (2). Cardiovascular diseases may be an important cause of mortality and morbidity in patients after HSCT owing to the toxicities of the cancer therapies; however, the incidence of cardiovascular events (CVEs) in this population has not been completely characterized. The objective of this systematic review is to summarize the evidence on the incidence of CVEs in HSCT recipients. Methods: Medline and Embase were searched from inception to December 2020 without language restriction. Two authors independently screened the titles and abstracts. Inclusion criteria were: cohort studies and phase 3 randomized controlled trials that reported CVEs (i.e., heart failure, arrythmias, acute coronary syndrome, and stroke) or cardiovascular death among adults who underwent HSCT for a hematological malignancy. All-cause mortality, relapse-related mortality, and non-relapse-related mortality (NRM) were also collected. Studies in which the follow up period was not started immediately after HSCT were excluded due to the risk of immortal bias. Results: Of 8151 nonduplicate articles, 30 studies including 14019 individuals post autologous HSCT, and 22 studies including 31049 individuals post allogeneic HSCT met the inclusion criteria. The cumulative incidence of CVEs in the first 100 days post autologous HSCT was 9% and arrhythmia (i.e., atrial fibrillation) was the most common CVE. In recipients of allogeneic HSCT, the 100-day cumulative incidence of CVEs was 3%, and heart failure (HF) was the most common reported CVE. In recipients of autologous and allogeneic HSCT, cardiovascular death was responsible for 43% and 10% of NRM within 100 days, respectively (Table 1). The incidence of CVEs was 4.96 per 1000-person years (95% CI; 4.21–5.80) in long-term survivors (beyond 100-days) of autologous HSCT, and HF was the most common CVE in this population. In long-term survivors of allogeneic HSCT, the incidence of CVEs was 1.90 per 1000-person years (95% CI: 1.59–2.24). Cardiovascular death was the most frequently reported CVE in long-term survivors of allogeneic HSCT (Table 2). Conclusion: CVEs remain a major cause of non relapse morbidity and mortality in recipients of HSCT, especially recipients of autologous HSCT within the first 100 days. Future studies are needed to identify the risk factors for CVEs that are specific to HSCT recipients. FUNDunding Acknowledgement: Type of funding sources: None.